Pengaruh pemberian pupuk Fe terhadap pertumbuhan, produksi, dan kelayakan ekonomi tanaman tomat (Solanum lycopersicum) - Hafith Furqoni (Fakultas Pertanian Universitas Majalengka, 2025)
Plants require nutrients to carry out various essential physiological processes in their lives. Iron (Fe) is one of the important micronutrients that are essential for plant growth and reproduction. Although plants only need Fe in relatively small amounts, compounds containing Fe play a crucial role in various physiological processes. The purpose of this study was to determine the effectiveness of Fe fertilizer on yield and economic feasibility in tomato plants. The experiment was arranged in a randomized block design with 7 treatments and 4 replications. The treatments used were without inorganic fertilization (P0), comparison inorganic fertilization (P1), and 5 levels of inorganic Fe fertilization: 1.0, 1.5, 2.0, 2.5, and 3.0 l/ha of inorganic Fe fertilizer applied at 4, 6, 8, and 10 weeks after planting (WAP). The results of the experiment showed that the application of 1.25 doses of inorganic Fe fertilizer (2.5 l/ha/application) resulted in the highest plant growth and yield components and tomato yield compared to the control treatment. That treatment also showed the most effective dose agronomically and economically. The recommended dose for tomato plants is 2.5 l/ha/application applied 4 times, namely at 4, 6, 8, and 10 WAP by foliar spray.